2023
DOI: 10.3390/ijms241411379
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Polyethylene Nano/Microplastic Exposure on Human Vaginal Keratinocytes

Paola Pontecorvi,
Simona Ceccarelli,
Fabrizio Cece
et al.

Abstract: The global rise of single-use throw-away plastic products has elicited a massive increase in the nano/microplastics (N/MPLs) exposure burden in humans. Recently, it has been demonstrated that disposable period products may release N/MPLs with usage, which represents a potential threat to women’s health which has not been scientifically addressed yet. By using polyethyl ene (PE) particles (200 nm to 9 μm), we showed that acute exposure to a high concentration of N/MPLs induced cell toxicity in vaginal keratinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…Moreover, chronic exposure to these particles caused lasting alterations in DNA methyltransferases and demethylases, potentially impacting epigenetic regulation, aging, inflammation, and even malignant transformations. These findings underscore the toxic effects of N/MPLs on human keratinocytes and underline the importance of comprehensively evaluating the plastics used in hygiene products, especially for women, such as disposable period products [14]. N/MPLs also pose a substantial risk to the endocrine system by interfering with hormone production, release, transport, metabolism, and elimination.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, chronic exposure to these particles caused lasting alterations in DNA methyltransferases and demethylases, potentially impacting epigenetic regulation, aging, inflammation, and even malignant transformations. These findings underscore the toxic effects of N/MPLs on human keratinocytes and underline the importance of comprehensively evaluating the plastics used in hygiene products, especially for women, such as disposable period products [14]. N/MPLs also pose a substantial risk to the endocrine system by interfering with hormone production, release, transport, metabolism, and elimination.…”
mentioning
confidence: 80%
“…The detrimental effects of MPL absorption through the skin due to extensive contact with plastic particles from sources like dust, cosmetics, sanitary pads, and liquid hand cleansers is an area of ongoing investigation [12,13]. In this regard, it was found that the acute exposure of vaginal keratinocytes to N/MPLs resulted in cell toxicity, affecting viability, apoptosis, gene expression, oxidative stress pathways, and miRNAs [14]. Moreover, chronic exposure to these particles caused lasting alterations in DNA methyltransferases and demethylases, potentially impacting epigenetic regulation, aging, inflammation, and even malignant transformations.…”
mentioning
confidence: 99%
“…To evaluate the presence of autophagosomes, autolysosomes or other vacuolar structures, we performed transmission electron microscopy (TEM) experiments, as previously described [ 42 ]. Briefly, RH30 and RD cells treated with SFX-01 (10–20 µM) or DMSO for 72 h were fixed in 2% glutaraldehyde (Electron Microscopy Sciences, Hatfield, PA, USA) in 0.1 M PBS for 24 h at + 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, dermal/skin contact needs to be considered because primary MPs, which are intentionally produced, were detected in products that people use daily such as cosmetics, toothpaste, skincare products, and even disposable period products [42,43]. However, ingestion is usually considered to be the primary route of exposure to microand nanoplastics.…”
Section: Human Health Threatmentioning
confidence: 99%